Impact of the COVID-19 Pandemic Era on Adolescent Mental Health - Hasni, Dita; Caesarian, Rafid Aqil; Maulana, Irfan; Febrianto, Budi Yulhasfi; Anissa, Mutiara (PT. Riset Press International, 2024)
The COVID-19 pandemic, driven by the spread of the SARS-CoV-2 virus, has brought about substantial global lifestyle changes. Governments worldwide have responded with various strategies, including the implementation of social distancing, which necessitates maintaining physical distance and limiting social interactions to curb virus transmission. This study seeks to assess the pandemic's effects on adolescent mental health and identify potential strategies for fostering positive mental well-being during these trying times. Utilizing systematic review and literature methods, data were collected from research journals conducted by experts and sourced from two databases, Google Scholar and PubMed. The findings indicate a notable impact of the COVID-19 pandemic on adolescent mental health, with disruptions in daily routines, especially due to distance learning resulting from social distancing measures, contributing to increased mental health issues such as depression, anxiety, and trauma among adolescents. In conclusion, this analysis, based on a review of 12 pertinent articles, underscores the significant influence of the COVID-19 pandemic on adolescent mental health. Effective efforts aimed at promoting positive mental well-being during this crisis require further attention to mitigate the resultant negative consequences. Further research and tailored preventive measures are crucial for assisting adolescents in navigating the mental health challenges posed by this ongoing pandemic.